2005
DOI: 10.1086/428939
|View full text |Cite
|
Sign up to set email alerts
|

A Multiwavelength Study of the X‐Ray Sources in NGC 5018

Abstract: The E3 giant elliptical galaxy NGC 5018 was observed with the Chandra X-Ray Observatory's Advanced CCD Imaging Spectrometer for 30 ks on 2001 April 14. Results of the analysis of these X-ray data as well as of complementary optical, infrared, and radio data are reported. Seven X-ray point sources, including the nucleus, were detected. If they are intrinsic to NGC 5018, then all six nonnuclear sources have luminosities exceeding 10 39 ergs s À1 in the 0.5-8.0 keVenergy band, placing them in the class of ultralu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…They found that the diffuse X-ray emission is spatially coincident with strong Hα emission, suggesting that it is powered by star formation. Ghosh et al (2005) obtained a good fit for the spectrum of the diffuse light with a MEKAL plus power law model with Galactic absorption. For the MEKAL component they found kT = 0.41 ± 0.04 keV.…”
Section: Mrk 231 (Iras 12540+5708)mentioning
confidence: 91%
See 2 more Smart Citations
“…They found that the diffuse X-ray emission is spatially coincident with strong Hα emission, suggesting that it is powered by star formation. Ghosh et al (2005) obtained a good fit for the spectrum of the diffuse light with a MEKAL plus power law model with Galactic absorption. For the MEKAL component they found kT = 0.41 ± 0.04 keV.…”
Section: Mrk 231 (Iras 12540+5708)mentioning
confidence: 91%
“…It is listed as E3: in the RC3 and in NED, but was classified as an SAB0-by Buta et al (2010) based on Spitzer 3.6 µm images. In short wavelength Spitzer images (Kim et al 2012) and in optical images (Ghosh et al 2005), a tail-like structure extends to the northwest. NGC 5018 was identified as a very latestage major merger remnant by Schweizer et al (1990) and Buson et al (2004).…”
Section: Mrk 231 (Iras 12540+5708)mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, optical photometric and spectroscopic studies have revealed that stars, star clusters, ionized nebulae, etc. are possible optical counterparts of ULXs (Ghosh et al 2001(Ghosh et al , 2005Ptak et al 2006;Ramsey et al 2006). Optical spectroscopic studies on the local environments of some ULXs have detected different emission lines, which suggest that both shock and photo-ionization excitations are the dominant physical processes around these objects (Abolmasov 2007a,b;Mucciarelli et al 2005Mucciarelli et al , 2007Zepf et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We used the METRIC program 1 to determine the relative positional errors (∼0. ′′ 27) between the PC1 and WF3 images (Ghosh et al 2005). The resultant astrometric accuracy is less than 0.…”
Section: Hubble Wfpc2 Observationsmentioning
confidence: 92%